Automatic aircraft landing control using nonlinear energy method - Jones, Lim Jen Nee; Akmeliawati, Rini; Tan, Chee Pin (IEEE, 2010)
This paper presents the integration of longitudinal and lateral dynamics controller designed using Nonlinear Energy Method (NEM) for a research civil aircraft. This controller ensures the core attitudes of the aircraft such as roll, pitch, yaw and airspeed follows their reference value determined by the given ﬂight trajectory for a landing approach. The NEM is supplemented with a positional tracker on the outer loop to facilitate better positional tracking. The robustness and disturbance rejection of the proposed controller is tested in different ﬂight conditions. Simulation result shows that the NEM is stable under scenarios such as a one-sided engine failure, a 90-degree turn, glideslopes and a wind shear. Positional tracking is also achieved in both normal and ‘extreme’ ﬂight conditions.